The Role of International Trade in Employment Growth in Micro- and Small Enterprises: Evidence from Developing Asia - Jens Krüger (Asian Development Bank (ADB), 2013)
This paper examines the role of international trade in employment growth in micro- and small enterprises using a representative sample of manufacturing firms in six Southeast Asian countries. After controlling for firm and individual characteristics as well as country and sector dummies, participation in international trade plays a significant role in explaining this growth, boosting firm-level growth by 3% per year on average. The fact that firms start exporting quickly after their foundation suggests that reverse causality is not an issue for our estimates. However, biases arising from unobserved heterogeneity cannot be ruled out. Therefore, we exploit the fact that firms were exposed to unexpected variation in real exchange rates between 2005 and 2008 to investigate the causal relationship between trade and employment growth. The results are not conclusive, but they do not suggest that the relationship is driven by unobserved heterogeneity.
hdl:11540/2307
Keywords: D22; O12; 330; MSE graduation; trade; employment growth